THE IMPACT OF THE FINANCING TO DEPOSIT RATIO AND CURRENT RATIO ON THE PROFITABILITY OF ISLAMIC BANKS: THE MODERATING ROLE OF NON-PERFORMING FINANCING - Budi Kolistiawan; Agus Eko Sujianto; Dede Nurohman; Eka Ratna Glis Purnamasari; Hardining Estu Murdinar; Larasati Widoningtyas (Academic Bright Collaboration, 2026)
This study aims to examine the effect of the Financing to Deposit Ratio (FDR) and Current Ratio (CR) on the profitability of Sharia Commercial Banks in Indonesia, with Non-Performing Financing (NPF) serving as a moderating variable during the 2019–2023 period. The study is motivated by the relatively lower profitability performance of Islamic banking compared tho conventional banking. This research employs a quantitative approach with an associative research design. The study uses secondary data derived from the annual financial reports of six Sharia Commercial Banks registered with the Financial Services Authority (OJK) over a five-year period (2019–2023), resulting in 30 observations. The analysis incorporates lagged financial variables to capture the delayed effect of financial performance indicators on profitability. The results indicate that FDR has a negative but insignificant effect on profitability. In contrast, CR has a significant negative effect on profitability, suggesting that excessively high liquidity may suppress profit performance. NPF shows a negative and significant effect on profitability in the baseline model; however, its effect becomes insignificant in the moderated regression model. Furthermore, NPF weakens the relationship between FDR and profitability, indicating that higher financing risk reduces the effectiveness of financing distribution in generating profits. However, NPF does not moderate the relationship between CR and profitability, meaning that the fourth hypothesis (H4) is not empirically supported. These findings emphasize the importance of maintaining a balance between financing distribution and financing quality, as well as optimizing liquidity management to prevent idle funds. Effective control of NPF is essential for maintaining the stability and financial performance of Islamic banks. This study contributes to the Islamic banking literature by simultaneously examining the moderating role of NPF in the relationship between FDR, CR, and profitability using the most recent data from the 2019–2023 period and incorporating lagged variables to provide a more comprehensive understanding of profitability dynamics in Islamic banking in Indonesia.